THE ROLE OF EMOTIONS IN LANGUAGE TEACHING (Web of Teachers: Inderscience Research, 2025)
Emotions are a vital part of the journey for both language teachers and learners, yet they often take a backseat in discussions about language acquisition. Traditionally, the focus has been more on cognitive skills, but the recent shift known as the ‘affective turn’ in applied linguistics is changing that. This shift emphasizes how emotions shape the way teaching and learning unfold. This article dives into the various emotions that teachers and learners’ experience, what triggers these feelings, and how they impact the learning process. It reviews important theories and research related to emotions in teaching and learning, as well as in teacher development. It also offers practical methods for building emotional competence—essentially, the ability to understand and manage emotions effectively in the context of language education.